The impact of hydraulic bores and debris on free standing structures - Nouri, Younes (University of Ottawa (Canada), 2008)
As tsunami waves travel towards the shoreline, they may break offshore and runup the shore as a hydraulic bore. Recorded videos from the December 26, 2004 Indian Ocean Tsunami show that tsunami waves transformed into a hydraulic bore that propagated onshore with considerably high velocity. Large pieces of debris such as boats were carried up to four kilometers inland. The 2004 December Indian Ocean Tsunami severely affected communities bordering the Indian Ocean, including the coasts of Indonesia, India, Sri Lanka, Thailand, the Maldives Islands, as well as the littoral zones of several West African countries. The performance of structures built in the vicinity of shorelines in these countries highlights the fact that current structural design codes do not give proper attention to tsunami-induced forces and the impact of floating debris. Currently, there are no clearly established procedures to address tsunami-induced forces. In this study, the deficiencies and discrepancies within tsunami-resistant design of typical buildings among the existing structural codes are identified. Currently, analogies between a tsunami-induced bore and a dam-break wave exist in literature. Therefore, in order to advance the existing understanding of bore-structure interactions, an experimental approach was taken where a dam-break flow, generated by the fast opening of a gate, impacts various free standing structures of different shapes located downstream of the gate. The pressures and forces exerted on all sides of the structure, together with the bore height and the flow velocities in the flume were measured. The effect of upstream obstacles and flow constrictions was also investigated. In addition, to further understanding of debris impact during a tsunami, wooden logs were added to the bore in order to act as water borne missiles while the structure reactions were measured. The present study aims to provide a better qualitative and quantitative understanding of tsunami-induced forces and debris impact in an effort to improve existing structural codes for the design of buildings that are located in the vicinity of the shoreline in tsunami prone areas.
Keywords: Engineering, Civil.